Nano-Sized Iron Sulfide: Structure, Synthesis, Properties, and Biomedical Applications - Yuan, Ye; Wang, Liping; Gao, Lizeng (Frontiers in Chemistry, 2020)
Nano-sized iron sulfides have attracted intense research interest due to the variety of their types, structures, and physicochemical properties. In particular, nano-sized iron sulfides exhibit enzyme-like activity by mimicking natural enzymes that depend on an iron-sulfur cluster as cofactor, extending their potential for applications in biomedicine. The present review principally summarizes the synthesis, properties and applications in biomedical fields, demonstrating that nano-sized iron sulfides have considerable potential for improving human health and quality of life.